Visualizing morphological structures of rice grains in precooked products using synchrotron radiation X-ray phase-contrast computed tomography. Issue 1 (12th December 2022) - Miki, Hiromi; Yoneyama, Akio; Hirano, Keiichi
Abstract : The morphology and internal structure of precooked rice products were successfully visualized without contrast agents by synchrotron radiation X-ray phase-contrast computed tomography (CT). Abstract : Rice is a staple food eaten by more than half of the world's population. In recent years, various types of precooked rice products have become commercially available as more and more people, including the elderly, do not have time to prepare meals or are coping with eating disorders. To address this situation, analysis of the internal structure of rice is important to understand the phenomena that occur during cooking rice grains and to develop rice products for specific purpose with desired physical properties. Although the internal structure of food has been observed by many methods, it is difficult to image the internal structure of rice porridge or rice grains with sufficient spatial resolution in a nondestructive manner. In this study, we applied X-ray interferometer-based phase-contrast computed tomography for the nondestructive observation of precooked rice products. For comparison, X-ray absorption-contrast images were also observed. The samples consisted of packaged aseptic cooked rice, precooked rice porridge for the general public, and a texture-modified rice product for people with dysphagia. In the phase-contrast two-dimensional (2D) tomographic images, the central lines of the cooked rice grains were successfully observed in all samples. The changes in the peripheral regions and internal hollows of the cooked rice grains were also clearly observed. Meanwhile, rice grains were hardly discernible in the X-ray absorption images. These results indicate that X-ray interferometer-based phase-contrast imaging is a promising tool for analyzing the morphology and internal structure of cooked rice grains in various prepacked products such as rice porridge and texture-modified rice.